2011
DOI: 10.1002/jemt.20881
|View full text |Cite
|
Sign up to set email alerts
|

Depth‐dependent anisotropies of amides and sugar in perpendicular and parallel sections of articular cartilage by Fourier transform infrared imaging

Abstract: Full thickness blocks of canine humeral cartilage were microtomed into both perpendicular sections and a series of 100 parallel sections, each 6 μm thick. Fourier Transform Infrared Imaging (FTIRI) was used to image each tissue section eleven times under different infrared polarizations (from 0° to 180° polarization states in 20° increments and with an additional 90° polarization), at a spatial resolution of 6.25 μm and a wavenumber step of 8 cm−1. With increasing depth from the articular surface, amide anisot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 36 publications
2
23
0
Order By: Relevance
“…This represented a near random organization of the fibrils and was consistent with the FTIRI results of the same cartilage sections [38]. Because of this low retardation, any angle measurement was likely to contain large errors, indicated by the large error bars in the angle profiles of parallel sections (Fig.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…This represented a near random organization of the fibrils and was consistent with the FTIRI results of the same cartilage sections [38]. Because of this low retardation, any angle measurement was likely to contain large errors, indicated by the large error bars in the angle profiles of parallel sections (Fig.…”
Section: Discussionsupporting
confidence: 82%
“…In the SZ cartilage, the collagen fibrils in parallel planes were found to have a finite structural anisotropy, established by the motional anisotropy of water molecules in μMRI [44] and the amide anisotropy in Fourier-transform infrared imaging (FTIRI) [36, 38]. These previous assessments of the surface fibril structure by different physical mechanisms are consistent with the birefringent results in this PLM report.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…In AC, the polarized FTIR studies have revealed that the intensities of the amide I, the amide II, and the amide III regions vary strongly when polarization plane of infrared light is altered (19,(57)(58)(59)(60), whereas the carbohydrate region shows only weak anisotropy in the radial zone of AC (58,61). It is known that the transition moments of the amide I and II bonds are qualitatively perpendicular to each other (60).…”
Section: 448 CMmentioning
confidence: 99%